Partially Awakened Giants: Uneven Growth in China and India - Chaudhuri, Shubham (World Bank, Washington, DC, 2012)
The paper examines the ways in which recent economic growth has been uneven in China and India and what this has meant for inequality and poverty. Drawing on analyses based on existing household survey data and aggregate data from official sources, the authors show that growth has indeed been uneven-geographically, sectorally, and at the household level-and that this has meant uneven progress against poverty, less poverty reduction than might have been achieved had growth been more balanced, and an increase in income inequality. The paper then examines why growth was uneven and why this should be of concern. The discussion is structured around the idea that there are both "good" and "bad" inequalities-drivers and dimensions of inequality and uneven growth that are good or bad in terms of what they imply for both equity and long-term growth and development. The authors argue that the development paths of both China and India have been influenced by, and have generated, both types of inequalities and that while good inequalities-most notably those that reflect the role of economic incentives-have been critical to the growth experience thus far, there is a risk that bad inequalities-those that prevent individuals from connecting to markets and limit investment and accumulation of human capital and physical capital-may undermine the sustainability of growth in the coming years. The authors argue that policies are needed that preserve the good inequalities-continued incentives for innovation and investment-but reduce the scope for bad ones, notably through investments in human capital and rural infrastructure that help the poor connect to markets.